Sic est (non) iusta causa belli? Issues of Law and Justice in the Debate Concerning a Roman Annexation of Egypt in 65 BC - Chrustaljow, Wjatscheslaw K. (Hyperboreus, 2019)
The author examines an episode associated with censor Crassus’ proposal in 65 BC to annex the Ptolemaic kingdom, concentrating mainly on the speciﬁc content of the debates between proponents and opponents of the annexation. The surviving fragments of Cicero’s speech De rege Alexandrino, as well as the Bobbio scholiast’s commentary on it, make clear that participants in the polemic appealed not only to law, but also to justice. The usage of such argumentation when discussing important foreign policy matters demonstrates once again that Romans of the Late Republic, at least in theory, wanted their wars to be ethically justiﬁed; the well-known Roman concept of bellum iustum was not of a purely formal character in that period, as some scholars believe.